Hadith #2951 - Sahih Muslim - Suwaid bin Ghafala (Sahih Muslim)
I saw Umar (Allah be pleased with him) kissing the Stone and clinging to it and saying: I saw Allah’s Messenger (ﷺ) having great love for you.
Grade: Sahih

Hadith #4174 - Sahih Muslim - Suwaid bin Ghafala (Sahih Muslim)
Don’t you know that it is forbidden (to strike the) face. He said: You see I was the seventh one amongst my brothers during the lifetime of Allah’s Messenger (ﷺ), and we had but only one servant. One of us got enraged and slapped him. Thereupon Allah’s Messenger (ﷺ) commanded us to set him free.
Grade: Sahih

Hadith #5278 - Sahih Muslim - Suwaid bin Ghafala (Sahih Muslim)
‘Umar addressed us at a place known as Jabiya (Syria) and he said: Allah’s Apostle (ﷺ) forbade us the wearing of silk but to the extent of two or three fingers or four fingers.
Grade: Sahih